A simple snowmelt parameterization for an Arctic site - Nardino, M.; Georgiadis, T. (Societa italiana di fisica, 2004)
Daily snow melt rates and corresponding changes in snow depth were determined through micrometeorological measurements of surface radiation and energy partition at Ny-˚Alesund (Svalbard Islands) during a short experimental campaign. The daily rates computed using micrometeorological techniques closely match direct measurements of snow depths with a mean error of about 6%. The present findings are relevant in Polar areas because of the extreme susceptibility of the local environment to sudden changes of surface properties, namely as regards to the regulation of the sea ice- atmosphere-ocean system and surface biological activity. The simple parameterizations utilized are suitable to model the short-time melting process.